All-cause mortality of patients with STEMI, cardiogenic shock and multivessel coronary disease treated with culprit vessel only versus multivessel primary PCI. (3rd October 2022) - Hlinomaz, O; Motovska, Z; Kala, P; Hromadka, M; Precek, J; Mrozek, J; Cervinka, P; Kettner, J; Matejka, J; Zohor, A; Bis, J; Jarkovsky, J
Abstract: Background: Patients with ST elevation myocardial infarction (STEMI) and cardiogenic shock (CS) treated with primary percutaneous coronary intervention (pPCI) have high mortality. A recent trial demonstrated that a culprit vessel-only strategy (CV-pPCI) was superior to immediate multivessel PCI (MV-pPCI) for patients with CS and multivessel coronary artery disease (MVD). Irrespective of it and current guidelines, multivessel PCI is still often used in these patients. Purpose/Methods: The study aimed to compare the characteristics and prognosis of patients with CS-STEMI and MVD treated with culprit vessel only pPCI or multivessel PCI during initial procedure. From 2016 to 2020, 23703 primary PCI patients with STEMI were included in the national all-comers registry of cardiovascular interventions. From them, a total of 1213 (5.1%) patients had cardiogenic shock and MVD at admission to the hospital. Initially 921 (75.9%) patients were treated with CV-pPCI and 292 (24.1%) with MV-pPCI. Results: CV-pPCI was a preferred strategy to MV-pPCI in men (74.6% vs 25.4%; p<0, 001) and women (79.8% vs 20.2%; p<0, 001) with CS-STEMI and MVD. Patients with 3-vessel disease and left main disease had higher probability to be treated with MV-pPCI than patients with 2-vessel disease and without left main disease (28.5% vs 18.6%; p<0, 001 and 37.7% vs 20.6%; p<0, 001).The CV-pPCI and MV-pPCI group patients did not differ in age (68.1±11.2 vs 66.2±11.4 years; p=0.780), previous PCI (16.1% vs 12.0%; p=0.890) and CABG (6.2% vs 4.8%; p=0.376), chronic kidney disease (6.8% vs 8.2%; p=0.426), cardiopulmonary resuscitation (60.4% vs 58.9%; p=0.657) and pulmonary ventilation (66.8% vs 70.5%; p=0.227) at admission, localization of myocardial infarction (anterior 50.8.% vs 58.9%; p=0.671), time to reperfusion (<2 hours 5.2% vs 4.8%; p=0.722) and TIMI flow 0 before PCI (63.1% vs 64.0%; p=0.675). Based on the results of logistic regression analysis, 30-days (odds ratio, 0.99; 95% CI 0.76 to 1.29; p=0.937) and 1-year (odds ratio, 0.91; 95% CI 0.69 to 1.19; p=0.477) all-cause mortality rates were similar in CV-pPCI and MV-pPCI groups. The presence of 3-vessel disease was the strongest adjusted predictor of 30-days (odds ratio, 1.61; 95% CI 1.27 to 2.04; p<0.001) and 1-year (odds ratio, 1.64; 95% CI 1.30 to 2.08; p<0.001) all-cause mortality in patients with STEMI and CS treated with pPCI. Conclusion: Immediate multivessel primary PCI is still used in patients with CS-STEMI and MVD in routine clinical practice. We did not find difference in 30-days and 1-year mortality among patients with CS-STEMI and MVD treated either with culprit vessel-only or multivessel primary PCI. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): NV19-02-00086 supported by Ministry of Health of the Czech Republic